The Berenstain bear scouts scream their heads off - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923- Berenstain Bear Scouts., 1998)
The Bear Scouts stand to inherit the valuable Spook Hill property from the Widow Bearkin if they can fulfill the stipulation in her will that they spend one night in the house to prove it is not haunted, but the Scouts are not at all sure they are up to the challenge.